VALUES AND AESTHETIC FACTORS IN THE FORMATION OF CULTURE AND ART - I. F. Kayumov (International Engineering Journal For Research & Development, 2020)
This dissertation shows the importance of raising the spiritual potential of young people, analyzes the system of tools that shape their spirituality, is an integral part of the spirituality of art, and all types of factors that increase the spiritual potential of young people. It is especially about art in the development of its potential. The ways in which universal spirituality, values ​​and aesthetic education influence the upbringing of theyounger generation through the world of music are described in the teachings of our ancestral scholars.